Kontrolni pregledi pri bolnikih z rakom v dolgotrajni remisiji - Drusany Starič, Kristina (Medicinski razgledi, 2003)
Oncologists in foreign countries have been gradually abandoning routine check-ups of cancer patients in long-term remission because, even today, thereis insufficient evidence of the effect of such check-ups on patients' survival and quality of life. In order to shed light on their difficulties,148patients were surveyed who had been in remission for more thanfive years after a confirmed malignancy. The goal was to find out what their feelings were concerning the check-ups, and in particular if they would trust their oncologist that such check-ups were no longer necessary. One of our essential questions was: What would be the patient's response? The study revealed that 40% of the patients would have felt relieved upon hearing that regular follow-up visits were no longer needed. However, 30% of them would have felt discriminated against and unprotected. Based on all of the above, wecame to a conclusion that a decision to stop further check-ups should be made only with the patient's approval.
Keywords: Neoplasms; Bolnik, zadovoljstvo; Health Surveys; Novotvorbe; tumor; Zboljšanje, vzpodbuditev; Remission Induction; Patient Satisfaction; Zdravstveni pregledi; Physician-Patient Relations; ankete; Questionnaires; Zdravnik-bolnik, odnosi; rak (medicina)